2020
DOI: 10.1101/2020.04.13.20062760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimates of regional infectivity of COVID-19 in the United Kingdom following imposition of social distancing measures

Abstract: We describe regional variation in the reproduction number of SARS-CoV-2 infections observed using publicly reported data in the UK, with a view to understanding both if there are clear hot spots in viral spread in the country, or other spatial patterns. Based on case data up to the 9th April, we estimate that the viral replication number remains above 1 overall in the UK but that its trend is to decrease. This suggests the peak of the first wave of COVID-19 patients is imminent. We find that there is significa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 22 publications
1
34
1
Order By: Relevance
“…Similar to most other COVID-19 models, we use a variant on a susceptible-exposed-infectious-recovered structure. 8–10 16 26 32 33 We do not spatially structure the population as in other UK modelling, 9 10 but we do include age-specific mixing based on POLYMOD data 22 and the postlockdown CoMix study. 11 We also explicitly measure the total asymptomatic infection, and the total in each of the clinically relevant hospital classes (acute or IC), which is a strength of our approach.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar to most other COVID-19 models, we use a variant on a susceptible-exposed-infectious-recovered structure. 8–10 16 26 32 33 We do not spatially structure the population as in other UK modelling, 9 10 but we do include age-specific mixing based on POLYMOD data 22 and the postlockdown CoMix study. 11 We also explicitly measure the total asymptomatic infection, and the total in each of the clinically relevant hospital classes (acute or IC), which is a strength of our approach.…”
Section: Discussionmentioning
confidence: 99%
“…8 A more recent study factoring spatial distribution of the population indicated the peak to follow in early April due to reducing to below 1 in many settings in weeks following lockdown. 9 Other modelling indicated that deaths in the UK would peak in mid-late April; furthermore, that the UK would not have enough acute and IC beds to meet demand. 35 While modelling from the European Centre for Disease Prevention and Control estimated peak cases to occur in most European countries in mid-April, 20 these estimations were largely at a national level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations